Biosynthesis of Ag/MWf-CNT Nanocomposites Using Aspergillus fumigatus as the CO Oxidation Catalyst. Issue 3 (3rd March 2016) - Yousefi, Naser; Pazouki, Mohammad; Alizadeh, Mehdi; Hesari, Fereydoon alikhani
Abstract : In this research, the biosynthesis process of an Ag nanoparticles/multiwalled carbon nanotubes (Ag/MWf-CNT) catalyst system has been investigated by Aspergillus fumigatus fungus. Characteristic peaks of pure silver and FCC crystallization systems were characterized by X-ray diffraction pattern. TEM images show a well-dispersed spherical silver nanoparticles (≤10 nm) on the carbon nanotubes. Based on the results, reduction of silver ions is mainly dependent on the biomass weight applied in the biosynthesis process. Catalytic activity in CO/CO2 conversion process revealed approximately 100% conversion of CO at 220°C.